2011
DOI: 10.1364/ao.50.003505
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field sensors utilizing coupling between a D-fiber and an electro-optic polymer slab

Abstract: This paper provides a detailed analysis of electric field sensing using a slab-coupled optical fiber sensor (SCOS). This analysis explains that the best material for the slab waveguide is an inorganic material because of the low RF permittivity combined with the high electro-optic coefficient. The paper also describes the fabrication and testing of a SCOS using an AJL chromophore in amorphous polycarbonate. The high uniform polymer slab waveguide is fabricated using a hot embossing process to create a slab wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…For high sensitivity to electric fields, the EO material used as the slab waveguide should have large EO coefficients and a low RF permittivity 8 . These parameters provide the greatest change to the index of refraction from an applied electric field.…”
Section: Scos Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For high sensitivity to electric fields, the EO material used as the slab waveguide should have large EO coefficients and a low RF permittivity 8 . These parameters provide the greatest change to the index of refraction from an applied electric field.…”
Section: Scos Theorymentioning
confidence: 99%
“…An analysis of the sensitivity of SCOS is discussed in Chadderdon, et al (2011), where two of the main contributing factors to the sensitivity are identified as the EO coefficients and RF permittivity of the slab waveguide. Previous work demonstrates SCOS fabricated using z-cut crystals and EO polymers, where the optic axes of the slabs are normal to the flat surface of the D-fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The non-intrusive nature of the sensor comes from the fact that, aside from electrodes, it is entirely built of dielectric materials. The size of the SCOS, only slightly larger than the optical fiber, allows precise field localization [2][3][4] and the sensor to be placed in virtually any environment suitable for an optical fiber.…”
Section: Introductionmentioning
confidence: 99%
“…SCOSs use resonant coupling of light between a D-shaped optical fiber and a nonlinear electro-optic (EO) slab waveguide [4]. The sensor consists entirely of dielectric materials and is only slightly larger than an optical fiber, which minimizes electric-field perturbation and results in precise field localization [5][6][7]. In addition, the small size enables the sensor to be placed in virtually any environment suitable for an optical fiber.…”
Section: Introductionmentioning
confidence: 99%